EcoProduction and Logistics Emerging Trends and Business Practices - Golinska, Paulina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Environmental awareness is driven mainly by the scarcity of natural resources and by more strict legal regulations. The modern enterprise policy should look at the relations between economic actions and ecological consequences. Ecoproduction is a new business approach which focuses on the most efficient and productive use of raw materials and natural resources in order to minimize footprints on the natural environment. This book aims to provide the state- of- the- art as well as new ideas of the environmental conscious operations management. The contributors present in the individual chapters problems related to: eco-friendly production technologies; recycling and waste reduction. Scope of topics discussed in this book covers also pollution prevention, energy efficiency. The authors describe problems of information management in complex systems
Sustainability and Life Cycle Management -- Environmental Friendly Resource Management in Production -- Information Systems and Information Management Supporting Sustainability.
Keywords: Environmental sciences; Environmental management; Biotechnology; Sustainable development; Environment; Environmental Engineering/Biotechnology.; Sustainable Development; Production/Logistics/Supply Chain Management; Environmental Management